Diversité sociale et tolérance à l’école - Guibet Lafaye, Caroline (Studi sulla Formazione/Open Journal of Education, 2011)
The author points out that some communities still do not accept the fact that in the world of education, their children are exposed to different lifestyles from their own. We must ask ourselves to what extent it is possible to respect for pluralism in school, the extent to which we must preserve the ability of everyone to benefit from an education for citizenship and pluralism. Then debate is open and very current.